Geophysical constraints on the thickness of the Holyrood Pluton, Avalon Peninsula, Newfoundland - Miller, H.; Pittman, D. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1982)
The vertical extent of the Holyrood Pluton and the surrounding Harbpur Main Group of the northeastern Avalon Peninsula of Newfoundland is estimated using two-dimensional gravity and magnetic models. The models are interpreted to indicate that the maximum thickness of the Holyrood Pluton is 1.8 km and that mafic Harbour Main volcanics must exist beneath the pluton and be confined to the uppnr 2.0 km of the crust west of the Conception/Cabot Group boundary on the eastern portion of the survey area.